The Responsibility of the Foreman for the Sale of Project Remaining Materials According to Wahbah Az-Zuhaili - Ahmad Riansyah Lubis; Sahmiar Pulungan (International Journal of Islamic Education, Research and Multiculturalism)
The issue of selling project leftover materials is an important part of project management and accounting that requires responsible supervision by the foreman. The concept of sharia-compliant accounting, as suggested by Wahbah Az-Zuhaili in the Islamic context, builds an ethical foundation for management that is in harmony with Islamic teachings. The purpose of this study is to determine the foreman's responsibility for the sale of Wahbah Az-Zuhaili's leftover materials. This type of research is a type of field research. The research methodology uses the type of field research (field research), namely the researcher goes directly to the place to be studied. The research location in the project research location in the Villa Mentari Kempinski Building Project Jalan Seksama Simpang Limun Medan, the research time was carried out from March to April 2024.  For data collection techniques the author conducts a library study (library research) and direct interviews with the Project Foreman regarding the sale of the remaining project materials. After the data is collected, the author analyzes and draws conclusions from the data collected. The results of the study found that after examining the losses in the Mentari Kempinski construction project, various reasons that contributed to the losses could be determined. Errors may have occurred in estimating the need for building materials, leading to an excess of wood and bamboo. A review of liability according to Az-Zuhaili, the foreman must be responsible for his actions, both in the world by receiving sanctions in accordance with company policy, as well as in the afterlife where he will be held accountable by Allah SWT for the breach of trust. This accountability includes returning goods or money obtained from illegal sales, as well as showing remorse and a commitment not to repeat similar actions.